2017
DOI: 10.1371/journal.ppat.1006645
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of melanization by serpin-5 and serpin-9 promotes baculovirus infection in cotton bollworm Helicoverpa armigera

Abstract: Melanization, an important insect defense mechanism, is mediated by clip-domain serine protease (cSP) cascades and is regulated by serpins. Here we show that proteolytic activation of prophenoloxidase (PPO) and PO-catalyzed melanization kill the baculovirus in vitro. Our quantitative proteomics and biochemical experiments revealed that baculovirus infection of the cotton bollworm, Helicoverpa armigera, reduced levels of most cascade members in the host hemolymph and PO activity. By contrast, serpin-9 and serpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 55 publications
8
91
0
Order By: Relevance
“…Similarly, cotton bollworm caterpillars were more susceptible to entomoviruses when they consumed corn than when they consumed cotton . In fact, such differences in susceptibility are closely related to insect immunity . Before an entomovirus kills an insect host, it must invade and overcome host immune responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cotton bollworm caterpillars were more susceptible to entomoviruses when they consumed corn than when they consumed cotton . In fact, such differences in susceptibility are closely related to insect immunity . Before an entomovirus kills an insect host, it must invade and overcome host immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Entomovirus indirectly affects the melanization of insect herbivores by reducing the melanization enzyme activity in insect hemolymph. For instance, inhibition of melanization by NPV infection in cotton bollworm caterpillars was due to reduced levels of PO activity in the infected host hemolymph . However, whether host plants affect the inhibition of melanization by NPV infection remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Vā€ATPase and lipase were found in the MEbrown module (resistant), and previous studies have shown that Vā€ATPase and lipase are involved in the silkworm defence response against BmNPV infection (Ponnuvel et al ., ; LĆ¼ et al ., ). Serpinā€5 was present in the MEsalmon module (susceptible), and previous research has indicated that overexpression of serpinā€5 promoted Helicoverpa armigera nucleopolyhedrovirus infection (Yuan et al ., ). Apart from the identification of potential antiviral genes, our data revealed potential insights into the underlying antiviral mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…These results indicated that Spn-2 may be involved in the B. mori antiviral response. Additionally, serpin-5 and serpin-9 can promote baculovirus infection by inhibiting melanizationin in Helicoverpa armigera [63]. Based on these findings, we speculated that the down-regulation of expression of Spn in resistant strains or following BmNPV infection might lead to inhibition of serine proteases and enhance host melanization to suppress infection by BmNPV in resistant strains.…”
Section: Non-enzymatic Proteins Response To Bmnpv Infection In Midgutmentioning
confidence: 92%